A Droplet‐Based High‐Throughput SERS Platform on a Droplet‐Guiding‐Track‐Engraved Superhydrophobic Substrate. Issue 7 (5th December 2016) - Shin, Sera; Lee, Jaehong; Lee, Sanggeun; Kim, Hyunchul; Seo, Jungmok; Kim, Dayeong; Hong, Juree; Lee, Soonil; Lee, Taeyoon
Abstract : A novel droplet‐based surface‐enhanced Raman scattering (SERS) sensor for high‐throughput real‐time SERS monitoring is presented. The developed sensors are based on a droplet‐guiding‐track‐engraved superhydrophobic substrate covered with hierarchical SERS‐active Ag dendrites. The droplet‐guiding track with a droplet stopper is designed to manipulate the movement of a droplet on the superhydrophobic substrate. The superhydrophobic Ag dendritic substrates are fabricated through a galvanic displacement reaction and subsequent self‐assembled monolayer coating. The optimal galvanic reaction time to fabricate a SERS‐active Ag dendritic substrate for effective SERS detection is determined, with the optimized substrate exhibiting an enhancement factor of 6.3 × 10 5 . The height of the droplet stopper is optimized to control droplet motion, including moving and stopping. Based on the manipulation of individual droplets, the optimized droplet‐based real‐time SERS sensor shows high resistance to surface contaminants, and droplets containing rhodamine 6G, Nile blue A, and malachite green are successively controlled and detected without spectral interference. This noble droplet‐based SERS sensor reduces sample preparation time to a few seconds and increased detection rate to 0.5 µ L s −1 through the simple operation mechanism of the sensor. Accordingly, our sensor enables high‐throughput real‐time molecular detection of various target analytes for real‐time chemical and biological monitoring. Abstract : A droplet‐based real‐time surface‐enhanced Raman scattering (SERS) sensor is developed based on superhydrophobic SERS‐active Ag dendritic substrate for high‐throughput biological and chemical molecular detection. The enhancement factor of the droplet‐based real‐time SERS sensor reaches 6.3 × 10 5, and droplets containing various molecules can be successively manipulated and clearly detected on the SERS sensor without cleaning process.